2016
DOI: 10.2217/fon-2016-0320
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mnk–eIF4E Pathway Sensitizes The Efficacy to Chemotherapy in Anaplastic Thyroid Cancer

Abstract: Targeting Mnk-eIF4E pathway provides a therapeutic strategy by sensitizing ATC response to chemotherapeutic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…eIF4E activation has been shown to be cellular survival mechanisms in response to various stress conditions, such as chemotherapy, in various types of tumors . However, little is known on whether eIF4E activation is involved in HCC cells in response to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…eIF4E activation has been shown to be cellular survival mechanisms in response to various stress conditions, such as chemotherapy, in various types of tumors . However, little is known on whether eIF4E activation is involved in HCC cells in response to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of EIF4E at Ser209 has been shown to be essential for EIF4E oncogenic activity. Earlier studies have shown that MNK kinase, downstream of MAPK pathway, can phosphorylate EIF4E at Ser209 (49, 50). Our results suggest that overexpression or inhibition of AURKA can affect the phosphorylation of EIF4E without changing MNK phosphorylation levels.…”
Section: Introductionmentioning
confidence: 99%
“…MNKs activity in thyroid cancer has been mainly associated with drug resistance mechanisms. In thyroid cancer cell lines, an increase in MNK-dependent eIF4E phosphorylation is observed after DNA damage by cisplatin [154] or by radionuclide therapy with radiolabeled gastrin analogs [151] and after inhibition of BET proteins, which function as transcriptional co-activators of oncogenic genes [155]. MNK inhibition or knockdown blocks the increased eIF4E phosphorylation and enhances the antitumor effects of these therapies in vitro [151] and in vivo [154,155].…”
Section: Mnk In Other Solid Tumorsmentioning
confidence: 99%
“…In thyroid cancer cell lines, an increase in MNK-dependent eIF4E phosphorylation is observed after DNA damage by cisplatin [154] or by radionuclide therapy with radiolabeled gastrin analogs [151] and after inhibition of BET proteins, which function as transcriptional co-activators of oncogenic genes [155]. MNK inhibition or knockdown blocks the increased eIF4E phosphorylation and enhances the antitumor effects of these therapies in vitro [151] and in vivo [154,155]. In addition, MNK inhibition or genetic depletion alone inhibits proliferation and induces apoptosis of anaplastic thyroid cancer cells, the most aggressive type of thyroid cancer, and reduces tumor growth in a mouse xenograft model [154].…”
Section: Mnk In Other Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation